PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP CORPORATE IMAGE AND REPURCHASE INTENTION DI PT. BANK SYARIAH MANDIRI THAMRIN JAKARTA - Ahmad Haekal (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
This research aims the customers who use saving products use to examine great influence of CSR toward corporate image and repurchase intention at BSM, Thamrin, Jakarta. All of the data is analized using structural equation modelling (SEM) supported by Lisrel version 8.72. Result from 135 respondents shows that CSR program able to strengthen and increase positive image for company. The activities CSR is capable to increase the repurchase intention for BSM product. Interestingly, the result shows that variable of CSR take significant effect to repurchase intention in Bank Syariah Mandiri (BSM), while variable corporate image doesn’t have a significant effect to repurchase intention and has not been able to increase the repurchase intention.